Strengthening children’s rights against fake news to reinforce democracy - Ahogado Alvarez, Ann-Christin (Przegląd Krytyczny, 2025)
Fake news is categorized as a menace to democracy and an object of scientific research in many ways—currently about the war in Ukraine. Russian narratives and concepts of competency in media are analyzed, but little about the reach and impact of fake news on the war in Ukraine on children’s rights. Therefore, this research analyzes fake news related to the war in Ukraine experienced by, or having an impact on, children in Germany and the consequences they have on children. This collective case study analyzes surveys, expert debates, EU policies against disinformation and media, and five conducted qualitative interviews. The presented study shows the need for children’s participation in Fake News to strengthen democracy and is of interest to political actors, industry, NGOs, media providers, and civil society.